HEALTH PRACTICES OF HIGH SCHOOL STUDENT IN KANYAKUMARI DISTRICT - N, Sudha; S.Padmakala (International Journal of Research -GRANTHAALAYAH, 2017)
The present study was conducted to know the health practices of high school students in Kanyakumari district. The investigator collected data from 420 high school students in Kanyakumari district. The data obtained were analyzed by using statistical techniques such as mean, standard deviation, t-test, ANOVA and correlation. The obtained results showed that there exists a moderate level of health practices among high school students in Kanyakumari district.